Expert Judgment of Learning Achievements Evaluation Instrument for Children Age 4-5 Years Old - Prima Suci Rohmadheny; Yunisa Laila (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2021)
This article discusses the results of expert judgment on the process of developing an evaluation instrument for the development of children aged 4-5 years based on the 2013 Early Childhood Education (PAUD) curriculum. The development of the instrument uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), but this research was carried out at the development stage. One of the development processes in this case is content validation through expert judgment. The expert judgment procedure is carried out by early childhood education experts. After the results of expert judgment are obtained, the researcher examines the indicator items that have been developed for improvement. The content validation was carried out on 186 items of child development achievement indicators that contained 6 aspects of the development of children aged 4-5 years and 46 basic competencies that were tied to 4 core competencies. As a result, as many as 186 of the indicator items received a score of 491 from a maximum score of 744 and a number of recommendations for improvement from experts. This means that the instrument is feasible to be continued at the implementation stage, namely the testing of the instrument, after minor repairs are made according to notes from the expert.